On Picard–Krasnoselskii Hybrid Iteration Process in Banach Spaces - Thabet Abdeljawad; Kifayat Ullah; Junaid Ahmad (Journal of Mathematics)
In this research, we prove strong and weak convergence results for a class of mappings which is much more general than that of Suzuki nonexpansive mappings on Banach space through the Picard–Krasnoselskii hybrid iteration process. Using a numerical example, we prove that the Picard–Krasnoselskii hybrid iteration process converges faster than both of the Picard and Krasnoselskii iteration processes. Our results are the extension and improvement of many well-known results of the literature.